PROCESS CAPABILITY ANALYSIS OF KATSUOBUSHI PRODUCTION AT PT. ABC - Soeharso, Agusta Putri Balqis Linda; Kuat, Pernika (Chanos Chanos, 2023)
Process capability in processing fishery products is a future challenge for the fishing industry, one of which is katsuobushi. The capability process refers to how a company can produce according to specifications to make it effective and efficient. The absence of process capability in the company is the basis for stating an effective and efficient process. The proposed study is to determine the company's current condition and provide suggestions for process improvement and evaluation. Through assumptions, this study influences the results of Cp and Cpk, which are calculated by Minitab software version 21st  as a method for measuring performance by identifying broad process tolerance production. In this study, the results for each data generated met data accuracy and standards. Still, at smoking 3rd and 4th stages, it was necessary to review specification values because of the value of Cpk < 1.00. As a result, after improving the standard by the six sigma concept, Cpk values are obtained > 1.00.